Summary: Political Legitimacy and Under-representation: How Do Citizens Evaluate the Political System - Talukder, David (Politics of the Low Countries, 2025)
The erosion of political support (Dalton, 2004) as well as the decline in citizens’ trust ingovernments and institutions (Bedock, 2017; Dalton, 1999, 2004; Norris, 2011; Pharr et al., 2000) is one major challenge for representative democracy. Indeed, scholars argue that support for democracy as a political regime is declining (Foa et al., 2020; Foa & Mounk, 2017), which questions to what extent representative democracies are able to resist democratic back-sliding. Building on this literature, the doctoral thesis aimed at providing a better understanding of citizens’ evaluation of the political system while engaging with recent scholarships linking unequal representation and citizens’ political attitudes (Ezrow & Xezonakis, 2011; Marié & Talukder, 2021; Mayne & Hakhverdian, 2017; Reher, 2016).